Design, Development and In Vitro Characterization of Self Emulsifying Drug Delivery System for Irbesartan: Design, Development and In-vitro Characterization of Self Emulsifying Drug Delivery System - Supriya Patil; Amol Shete; Vinit Patil; Rajendra Doijad (Iranian Journal of Pharmaceutical Sciences, 2013)
The objectives of present investigations were to optimize concentration of oil, surfactant and cosurfactant by pseudoternary phase diagrams and to develop a stable formulation of self emulsifying drug delivery system (SEDDS) in order to enhance the dissolution rate of poorly soluble Irbesartan (IBS) by SEDDS. Pseudoternary phase diagrams were constructed to identify the self emulsifying region. Four self emulsifying formulations were prepared using mixture of Capryol 90 as oil, Tween 80 as surfactant and PEG 400 as cosurfactant in various proportions. Optimized liquid SEDDS formulations were converted into free flowing powder by spray drying technique and evaluated for drug content, infrared spectroscopy (FTIR), differential scanning colorimetry (DSC), powder X-ray diffraction (PXRD), Zeta potential analysis, Particle size analysis, scanning electron microscopy(SEM),in vitro dissolution study and in vitro diffusion study. The results suggested that considerabl improvement in the dissolution rate of drug from optimized SEDDS formulation was attributed to decreased crystallinity, altered surface morphology and reduction in particle size. Optimal formulation of irbesartan SEDDS were successfully developed in this work. The study illustrated that potential use of SEDDS dispense lipid soluble drug by oral route.